Organizational Citizenship Behavior (OCB) Karyawan pada Perusahaan - Kusumajati, Dian Anggraini (Humaniora, 2014)
Human resources are the most important asset in a company to get success of an organization/company. Many organizations face challenges such as how organizations respond to change from external and adapt to internal environment of organization. In this case OCB can increase organizational performance, because this behavior is the "oil" of social machine of the organization. In other words, with this behavior in social interaction the member from organization can be smooth, reduce disputes, and improve efficiency. OCB is a voluntary behavior that exceeds workers? basic needs such as helping co-workers and courteous to others, which benefit an organization, and does not relate to the compensation system. The dimensions of OCB consist of altruism, conscientiousness, sportsmanship, courtesy, civic virtue. The factors affect the OCB, namely: culture and climate, personality and mood, organizational support, quality of interaction superiors and subordinates, tenure and gender. Implications of OCB are quality of service, performance groups, and turnover. The benefits from OCB to the company are improving the productivity of co-workers, increasing managers? productivity, saving management?s and organization?s resources, saving energy resources to maintain the group function, to be an effective facility to coordinate the activities of the working groups, improving the ability from organization to attract and maintain best employees, improving the stability of organizational performance, and enhancing the organization's ability to adapt environmental changes. It can be said that if the company wants to increase employee?s OCB, the company should pay attention to the factors that influence employee?s OCB and OCB implications to the company.